Geometry of an Intense Auroral Column As Recorded in Rock Art - van der Sluijs, Marinus; Johnson, Robert J. (Journal of Scientific Exploration, 2013)
In 2003, Peratt demonstrated that rock art images worldwide bear a remarkable similarity to high-energy plasma discharge formations. In later papers, Peratt located the plasma discharge column in which all of these would have occurred at the Earth’s South Pole. This article accepts the relation between the rock art images and the plasma formations, but concludes that the geometry of the reconstruction is incompatible with the global occurrence of the rock art images. As a corollary, the finer details of the reconstructed column must also be called into question. In particular, the reconstruction of the top cusp, the two upper plasmoids, and the filamentary sheath in a single column at the South Pole cannot be reliably deduced from the data as presented by Peratt. All evidence points to a worldwide distribution of the phenomena.